استقصاء واقع التلوث بنزر بعض العناصر المعدنية الثقيلة في مياه الصرف الصحي لمدينة اللاذقية (Latakia University Journal -Basic Sciences Series, 2018)
تناولت هذه الدراسة تحديد تراكيز نزر بعض العناصر المعدنية الثقيلة (Pb, Cu, Cr, Cd) في مصبات مياه الصرف الصحي لمدينة اللاذقية، وشملت ثلاثة مواقع في منطقة الرمل الجنوبي في فصلي الربيع والصيف من عام 2005. اعتمدنا في هذه الدراسة على مطيافية الامتصاص الذري (AAS) في تحديد نزر العناصر المذكورة أعلاه مستخدمين طريقة الاستخلاص (APDC-CHCl3) المتبعة للعينات المائية المدروسة وفق تقانة التذرية الكهرحرارية   (ETA-AAS). أظهرت الدراسة ارتفاع تراكيز عنصر الرصاص (6.60-45.43µg/l) في جميع المواقع المدروسة بالمقارنة مع تراكيز بقية العناصر، في حين سجل كل من عنصري الكروم والكادميوم تراكيز منخفضة نسبياً تراوحت بين (0.11-0.85µg/l) و (0.74-2.42µg/l) على التوالي. أظهرت الدراسة الإحصائية وجود علاقة ارتباط مرتفعة إلى منخفضة أحياناً وسلبية أحياناً أخرى مما يعطي مؤشراً واضحاً على أن نسبة الزيادة أو النقصان في تراكيز العناصر المدروسة ترتبط ارتباطاً وثيقاً بالتلوث الناجم عن مصادر النشاط البشري المختلفة. This study deals with identifying some traces heavy metals (Pb, Cu, Cr, Cd) in the effluent water of three sites in the southern region of Lattakia in the spring and summer of 2006. This research uses the (ETA-AAS) technique in determining the traces of heavy metal elements mentioned above using the following extraction method (APDC-CHCl3) for water samples. This paper has shown a higher concentration of Pb-element (6.60-45.43µg/l) in all studied sites compared with the concentration of other elements. However, Cr and Cd have recorded low concentrations ranged between (0.11-0.85µg/l) and (0.74-2.42µg/l), respectively. The statistical study has demonstrated that there is a correlation varying from positive high to positive low, and sometimes to negative highs and lows. This gives a clear indication that the increasing or decreasing ratios in the concentration of the studied elements in effluent water is very closely related to the pollution resulting from different sources of human activity.